Deindustrialization as Public History: An Exhibition at the Manitoba Museum - Reilly, Sharon (Urban History Review / Revue d'histoire urbaine, 2007)
The mass settlement and industrialization of southern Manitoba that began in the 1870s, and the reversal of much of this development in the twentieth century, is a major theme of the newest permanent gallery at the Manitoba Museum. This paper examines this history of industrial activity and deindustrialization and explores how these processes have been interpreted in the Parklands/Mixed Woods Gallery. Three distinct industries are considered: the Leary Brick Works in Roseisle, the Manitoba Glass Company of Beausejour, and Mary Maxim Limited, a mail-order woollens company that began in the village of Sifton.